1995
DOI: 10.1038/375146a0
|View full text |Cite
|
Sign up to set email alerts
|

Male–female differences in fertility and blood pressure in ACE-deficient mice

Abstract: Angiotensin-converting enzyme (ACE) is a dipeptidyl carboxy-peptidase that generates the vasoconstricting peptide angiotensin II and inactivates the vasodilating peptide bradykinin. The gene encoding ACE is composed of two homologous regions and codes for both a somatic and testis isoenzyme. Experiments with hypertensive rats and some, but not other, studies of humans suggest that sequences at or linked to the gene influence blood pressure. The testis-specific form of ACE has its own promoter within intron 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
414
2
6

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(434 citation statements)
references
References 23 publications
10
414
2
6
Order By: Relevance
“…These observations contrast with mice lacking all ACE who have both renal developmental defects and are unable to effectively concentrate urine. 2,3 Thus, the generation of angiotensin II in tissue locations independent of the renal parenchyma appears capable of maintaining cardiovascular homeostasis, including normal renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations contrast with mice lacking all ACE who have both renal developmental defects and are unable to effectively concentrate urine. 2,3 Thus, the generation of angiotensin II in tissue locations independent of the renal parenchyma appears capable of maintaining cardiovascular homeostasis, including normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Each of these parameters was studied in the ACE 8/8 mice. Systolic blood pressure was evaluated in conscious wild-type, heterozygous, and ACE 8/8 mice (Figure 6a).…”
Section: Physiological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a direct link between a particular gene impinging histone modifications to BP has not been clearly established. Second, numerous mouse models lacking ENaC and their direct or indirect regulators such as AS, 13 angiotensinogen (Agt), 14 angiotensin-converting enzyme (ACE), 15 MR, 16 Sgk1, 17 WNK1, 18 WNK4, 19 and Period 20 have been reported. However, the role of these models in showing the epigenetic control of BP is still unclear.…”
mentioning
confidence: 99%
“…Linkage studies in rodents (14,15) and case-control studies in humans (16,17) have suggested that sequences at, or linked to, the ACEgene (Ace) can influence blood pressure. The disruption of the Ace gene in mice demonstrated that the null mutants have comparably low blood pressure with Agt mutant (Agt-/~) mice (18,19).…”
Section: Confirmation Of Predicted Functions Of Ang IImentioning
confidence: 99%